Workload And Turnover Intention Of Employees Of Department X, Kaimana District - Bilie Francesco Yaas; Susana Prapunoto (UNIVERSITAS PAKUAN, 2025)
This study examines the correlations between workload and turnover intention among employees at Department X in Kaimana Regency. The research used a quantitative approach with a correlational design. The participants consisted of 70 employees selected through total sampling. Measurement tools included a workload scale and a turnover intention scale. Data analysis using Pearson correlation revealed a significant positive relationship between workload and turnover intention. The higher the perceived workload, the greater the employees' intention to leave the organization. This study is expected to provide practical contributions for Department X in creating a more balanced workload distribution strategy and reducing turnover intention in the workplace.